Small-Scale Fisher's Livelihood Strategies: Findings from Case Studies in Several Indonesian Coastal Areas - Hery Saksono; Suadi Suadi; Zulfa Nur Auliatun Nissa’ (Universitas Gadjah Mada, 2023)
Globally, small-scale fisheries have a substantial impacts on food security, nutrition, and well-being as well as the main livelihood for coastal communities. Due to widespread environmental changes, some 2.67 million Indonesia fishers who depend on small-scale fishing are vulnerable to poverty and environmental deterioration. This study summarizes the results of studies related to the analysis of the livelihoods of small-scale fishers through several case studies conducted by the Fisheries Socioeconomic Laboratory at the Department of Fisheries UGM, during 2015 to 2020. Such literature review was employed as the primary methodology in this study and it is essential for developing conceptual models for synthesizing research findings and identifying the areas for further investigation. The study examines the livelihoods of small-scale fishers with a focus on livelihood resources, responses to pressure on livelihood resources, and survival strategies. The study discusses on the livelihoods of small-scale fishers who actively engage in fishing activities with boats of approximately 10 GT, with 2 to 5 fishers per boat. The study found that most small-scale fishersonly have a basic education particularly elementary school, have no other employment options during bad weather, and are under pressure from a variety of environmental change factors. Small-scale fishers are particularly exposed to pressures from the weather, gear bans, rising fuel prices, and low levels of education, and overfishing. Small-scale fishing households adapt by reorganizing household tasks, utilizing various technology, and developing group organizations to avoid problems like territory disputes. The fishers also do this by requesting support and subsidies and actively partaking in religious activities. Local customs that forbid fishing on particular days are said to aid in the replenishment of fish stocks, making sea alms a safety net for fisher communities.